Declining Prevalence of Probable Depression Among Patients Presenting for Antiretroviral Therapy in Rural Uganda: The Role of Early Treatment Initiation - Chan, Brian T.; Weiser, Sheri D.; Boum, Yap; Haberer, Jessica E.; Kembabazi, Annet; Hunt, Peter W.; Martin, Jeffrey N.; Mocello, A. Rain; Bangsberg, David R.; Tsai, Alexander C. (AIDS and Behavior, 2015)
Little is known about trends in depression at antiretroviral therapy (ART) initiation among people living with HIV (PLHIV) in low- and middle-income countries. We used data from an ongoing cohort of treatment -naı¨ve PLHIV in rural Uganda to estimate secular trends in depression among PLHIV at ART initiation. We fitted linear regression models with depression symptom severity as the outcome variable and year of cohort entry (2005–2012) as the explanatory variable, adjusting for socio-demographic variables and assessing physical health score, body mass index (BMI), and CD4 count as potential mediators of a secular trend in depression symptom severity. There was a statistically significant negative association between year of entry and depression symptom severity, suggesting a 3.1 % relative decline in the mean depression symptom severity score at ART initiation in each year of study recruitment after the first year. This trend remained statistically significant after inclusion of baseline socio demographic characteristics to the model and appeared to be driven by improved physical health scores, but not CD4 count or BMI.
Keywords: Depression; Trends; Physical health; Antiretroviral therapy; HIV; Uganda